Discretization Envelope Design Modeling Method of Rack and Pinion with Variable Ratio - Dai Yin (Jixie chuandong)
A design method of discretization envelope is proposed for the variable ratio rack and pinion, a transverse profile model of helical gear is established as the gear shaper cutter and the generating motion of gear shaping is simulated to obtain the envelope point cloud of the variable ratio rack in Matlab. The data points in the envelope point cloud are very dense, and at the same height, the distance between the adjacent tooth profile points is far greater than that between the non-tooth profile points. Based on this, a new numerical algorithm for tooth profile point extraction is proposed. The process is intuitive and the coordinates of rack tooth profile point are determined to improve the accuracy. The program is optimized to greatly improve the efficiency of design and model. The simulation of the variable ratio rack and pinion based on Adams and proved the feasibility and correctness of the design method.